Preventing undesired eye formation in soft cheese - Gimenez, Paula (2021)
The ability of the adjunct culture Lacticaseibacillus paracasei 90 (L90) to prevent undesired eye formation by heterofermentative bacteria was assessed in soft cheeses, ripened either in normal conditions or with interruptions in the cold chain. Leuconostoc mesenteroides D11 isolated from defective cheeses with undesired eye production were added to control (C) and experimental (E) Cremoso soft cheeses to simulate the occurrence of high levels of adventitious heterofermentative bacteria; the adjunct culture L90 was added only to E cheeses. The presence of high levels of L90 affected the carbohydrates fermentation, and the levels of hippuric and benzoic acids. These changes produced an adverse environment for the undesirable activity of the strain D11. In effect, the incorporation of L90 decreased the metabolic activity of the D11 strain and consequently avoided the unwanted eye formation. The maintenance of an adequate cold chain was also an important factor to obtain cheese without eye defects.